Strategic Development Leader Potential in Community Enterprises of Kamphaeng Phet Province Strategic - Suwannarot, Armonrat; Dongtipya , Soontree; Nitnakon, Ratchanee (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2025)
The purposes of this research were to 1) study the conditions, the problems, and the factors related to the development of leader potential in community enterprises Kamphaeng Phet Province. 2) develop the strategy of leader potential in community enterprises, Kamphaeng Phet Province. 3) the strategy for developing leader potential in community Enterprise Kamphaeng Phet Province. The informants consisted of personnel of the Kamphaeng Phet Provincial. Agriculture office, personnel of the District Agriculture office the leaders of community enterprises in Kamphaeng Phet Provincial, personnel of the Lumphun Provincial Agriculture office and the leaders in community enterprise which had outstanding national community enterprises potential assessment results, academics who were the experts in human resource development and strategic development. The Research instruments were a questionnaire focus group, workshop connoisseurship, and strategic assessment from the data were analyze using frequency, percentage, mean, standard deviation and content analysis The results revered that the conditions of the development of leader potential in community enterprise, Kamphaeng Phet Province was there was the planning of developing leader potential in community enterprises with be setting the directions or the guidelines of potential development. The Plans were operated to achieve the goals. The evaluation was carried continuously. Evaluated results were considered for improving leader potential in community enterprises. The problems of the development of leader potential in community enterprises in Kamphaeng Phet Province was found that the goals of developing leader potential was unclear. Leaders in community enterpriser could not access the resources for developing there own potential. Leader in community enterprises. lacked the ability to evaluate their own progresses. The alternative for designing the development did not agree with the results, of evaluation. The factors related to the development of leader potential in community enterprises Kamphaeng Phet Province was found that The most relevant internal factors were personal characteristics and budget, while the most relevant external factors was technology.The strategy of leader potential in community enterprises Kamphaeng Phet Province consisted of 7 strategies as follows 1) upgrading the planning development process for participatory leader potential development, 2) promoting corporation with the government and private sectors in development 3) developing information with supported the development of community enterprises leader potential 4) increasing the competency of using information 5) supporting the activities for development leader potential 6) developing the process of evaluation for development leader potential 7) Developing informational database for development leader potential. The developed strategies had the agreement, the appropriateness the possibility and the utility at the highest level.